2023
DOI: 10.32479/ijefi.13527
|View full text |Cite
|
Sign up to set email alerts
|

Does External Debt Affect Economic Growth: Evidence from South Asian Countries

Abstract: Time series econometric methods are frequently used in studies examining how external debt affects economic growth. For the period of 1980-2020, this study creates a panel dataset of five South Asian nations and examines the link between external debt and economic growth. The findings of Cross-sectionally Augmented Panel Unit Root Test by Pesaran's (2007) confirms that all variables are integrated in order I (1). To understand the error correction mechanism that determines the short-run dynamic nature of exter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…There are no definite results in the studies that followed. While some studies (Macnair et al, 1995;Asseery, 1996;Brumm, 1997;Sezgin, 1997;Murdoch et al, 1997;Lai et al, 2002;Yildirim et al, 2005;Malizard, 2010;Alptekin and Levine, 2012;Canbay and Mercan, 2017;Ismail, 2017;Dimitraki and Win, 2021;Aijaz Syed, 2021) are for the Benoit hypothesis, the others (Faini et al, 1984;Deger, 1986;Dunne and Vougas, 1999;Dunne et al, 2002;Klein, 2004;Yang et al, 2011;D'Agostino et al, 2019;Dunne and Tian, 2015;Luqman and Antonakakis, 2021) are against the hypothesis. Besides, some other studies (Biswas and Ram, 1986;Alexander, 1990;Dakurah et al, 2001;Aye et al, 2014;Gokmenoglu et al, 2015;Manamperi, 2016) did not find sufficient evidence regarding the relationship between economic growth and military expenditures.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…There are no definite results in the studies that followed. While some studies (Macnair et al, 1995;Asseery, 1996;Brumm, 1997;Sezgin, 1997;Murdoch et al, 1997;Lai et al, 2002;Yildirim et al, 2005;Malizard, 2010;Alptekin and Levine, 2012;Canbay and Mercan, 2017;Ismail, 2017;Dimitraki and Win, 2021;Aijaz Syed, 2021) are for the Benoit hypothesis, the others (Faini et al, 1984;Deger, 1986;Dunne and Vougas, 1999;Dunne et al, 2002;Klein, 2004;Yang et al, 2011;D'Agostino et al, 2019;Dunne and Tian, 2015;Luqman and Antonakakis, 2021) are against the hypothesis. Besides, some other studies (Biswas and Ram, 1986;Alexander, 1990;Dakurah et al, 2001;Aye et al, 2014;Gokmenoglu et al, 2015;Manamperi, 2016) did not find sufficient evidence regarding the relationship between economic growth and military expenditures.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…According to the study results, defense expenditures increase economic growth in Middle East countries and Turkey. Ismail (2017) analyzed the impact of military expenditure on economic growth using the 1988-2013 data from five south Asian countries. According to the study results, military expenditures encouraged economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…They discovered that EXD had a favorable short-term link with Gross Domestic Product, however a poor long-term link. Ale et al (2023) used the CS-ARDL method on a panel of five SA countries for the period of 1980-2020 and concluded that a significant relation between EXD and EG exists, both in short run and long run.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another study carried out in Nigeria by Umaru, Hamidu, and Musa (2013) indicates that borrowed funds from other countries have insignificant negative effects on the Nigerian economy. Also, Shabbir (2009) did conduct a study in 24 African economies and realized that external debt exerted a negative effect on the economic growth of these countries.…”
Section: Descriptive Statistics and Diagnostic Testsmentioning
confidence: 99%